Value of statistical life year in extreme poverty: a randomized experiment of measurement methods in rural Burkina Faso [dataset] - Trautmann, Stefan T.; Xu, Yilong; König-Kersting, Christian; Patenaude, Bryan N.; Harling, Guy; Sié, Ali; Bärnighausen, Till (Universität, 2022)
Background: Value of a Statistical Life Year (VSLY) provides an important economic measure of an individual’s trade‑off between health risks and ot...
Gesehen am 25.01.2022
Keywords: Forschungsdaten; Datenbank